2015
DOI: 10.1007/s12017-015-8357-7
|View full text |Cite
|
Sign up to set email alerts
|

Are Molecules Involved in Neuritogenesis and Axon Guidance Related to Autism Pathogenesis?

Abstract: Autism spectrum disorder is a heterogeneous disease, and numerous alterations of gene expression come into play to attempt to explain potential molecular and pathophysiological causes. Abnormalities of brain development and connectivity associated with alterations in cytoskeletal rearrangement, neuritogenesis and elongation of axons and dendrites might represent or contribute to the structural basis of autism pathology. Slit/Robo signaling regulates cytoskeletal remodeling related to axonal and dendritic branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 66 publications
2
44
0
Order By: Relevance
“…Neuronal migration and morphogenesis defects in ASD contribute to an altered cortical connectivity in different brain regions [45] [46], as the well-known prefrontal area [47]. Therefore, in the developing brain, a premature alteration in neuronal plasticity, affecting mostly cortical regions involved in cognitive and behavioral functions, might trigger the autistic phenotype [48] [49].…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal migration and morphogenesis defects in ASD contribute to an altered cortical connectivity in different brain regions [45] [46], as the well-known prefrontal area [47]. Therefore, in the developing brain, a premature alteration in neuronal plasticity, affecting mostly cortical regions involved in cognitive and behavioral functions, might trigger the autistic phenotype [48] [49].…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of this turnover could be particularly affected in the neurodevelopmental disorders. It implicates that short-term multistep mechanisms underlying neuritogenesis, axon pathfinding, and dendritic spine motility, could be associated with autism spectrum disorders (Bakos et al 2015).…”
Section: Long-lasting Changes or Short-term Effects?mentioning
confidence: 99%
“…Although, it is still not fully understood, dysregulation of RhoA, Rac1, and Cdc42 may be a part of a mechanism involved in neurodevelopmental disorders. On the basis of analysis of publicly available microarray data, we have demonstrated a decreased expression of the Cdc42 in autistic subjects (Bakos, Bacova, Grant, Castejon, & Ostatnikova, ). Other bioinformatics data have shown that Cdc42 is a part of an interaction pathway associated with autism (Kalkan, Durasi, Sezerman, & Atasever‐Arslan, ).…”
Section: Alterations In Rho Gtpase‐mediated Pathways Contribute To Nementioning
confidence: 99%